Alur society - "Southall, Aidan W" (Cambridge, 1953)
Alur Society became a classic for a number of reasons. Being much more than a descriptive account of an African society, it was the first intensive ethnography to adopt the ideas of Max Weber. It pioneered the idea that religion and ritual could be the basis of political action. It also showed how state systems could evolve not just on the basis of conquest but as a result of societies without kings inviting those with kings to govern them. Author Aidan Southall's theory of the segmentary state was adopted by political anthropologists throughout the subject and also by political scientists, being applied not just to Africa but also to India and other parts of the world. The book was able to arrive at such long-lasting and imaginative conclusions through the use of ethnographic material of a quality rarely surpassed. It is moreover arguably the best book in social anthropology of a Nilotic-speaking people. Southall's own command of their language and his overall scholarly knowledge of Nilotes is also unsurpassed.
Keywords: Sociology